DETERMINAN MINAT MAHASISWA AKUNTANSI DALAM MENGGUNAKAN MOBILE BANKING (STUDI KASUS DI POLITEKNIK NEGERI SAMBAS) - Tri Wahyuni; Eliza Noviriani; Roshani, Roshani (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the influence of security, convenience, and benefits on the interest in using mobile banking, as well as the role of convenience as a moderating variable in students of the Corporate Financial Accounting Study Program at the Sambas State Polytechnic. The research method used is quantitative with a causal associative approach. Data were collected through an online questionnaire distributed to 190 respondents, and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique with SmartPLS software version 4. The results of the study indicate that benefits have a positive and significant influence on the interest in using mobile banking, while security and convenience do not have a significant effect. In addition, convenience does not act as a significant moderating variable in the relationship between security, convenience, and benefits on interest. The conclusion of this study is that generation Z, especially accounting students, prioritize functional aspects such as speed and efficiency in using mobile banking, while aspects of security, convenience, and convenience are considered standard features that should be there. Keywords: Security, Ease Of Use, Convenience, Benefits, Interest, Mobile Banking